Applied arts in British exile from 1933 : changing visual and material culture - Malet, Marian (Yearbook of the Research Centre for German and Austrian Exile Studies, 2019)
"Yearbook Volume 19 continues an investigation which began with Arts in Exile in Britain 1933-45 (Volume 6, 2004). Twelve chapters, ten in English and two in German, address and analyse the significant contribution of émigrés across the applied arts, embracing mainstream practices such as photography, architecture, advertising, graphics, printing, textiles and illustration, alongside less well known fields of animation, typography and puppetry. New research adds to narratives surrounding familiar émigré names such as Oskar Kokoschka and Wolf Suschitzky, while revealing previously hidden contributions from lesser known practitioners. Overall, the volume provides a valuable addition to the understanding of the applied arts in Britain from the 1930s onwards, particularly highlighting difficulties faced by refugees attempting to continue fractured careers in a new homeland. Contributors are: Rachel Dickson, Burcu Dogramaci, Deirdre Fernand, Fran Lloyd, David Low, John March, Sarah MacDougall, Anna Nyburg, Pauline Paucker, Ines Schlenker, Wilfried Weinke, and Julia Winckler"--